Teaching Mathematics To Students With Visual Impairment In Inclusive Education Schools In Jordan - Ghunaimat, Mohammad Ali (Papanda Publisher, 2024)
The students with visual disabilities is considered part of Jordanian society, and the Jordanian Constitution guaranteed that they are provided with all rights, including education. The study aimed to investigate the teaching of mathematics to students with visual disabilities in inclusive schools in Jordan. The researcher used the qualitative approach by conducting an interview with a mathematics teacher with long experience in teaching mathematics in inclusive schools. The results of the interview showed that there are ways and methods for teaching the content of mathematics curricula to students. People with visual impairment, and there is a positive impact and benefits of integrating students with visual impairment into inclusive schools, although there are some challenges facing students and mathematics teachers.